A Unique Mechanochemical Redox Reaction Yielding Nanostructured Double Perovskite Sr2FeMoO6 With an Extraordinarily High Degree of Anti-Site Disorder - Tóthová, Erika; Düvel, André; Witte, Ralf; Brand, Richard A.; Sarkar, Abhishek; Kruk, Robert; Senna, Mamoru; Da Silva, Klebson Lucenildo; Menzel, Dirk; Girman, Vladimír; Hegedüs, Michal; Baláž, Matej; et al. (Frontiers in Chemistry, 2022)
Strontium ferromolybdate, Sr2FeMoO6, is an important member of the family of double perovskites with the possible technological applications in the ﬁeld of spintronics and solid oxide fuel cells. Its preparation via a multi-step ceramic route or various wet chemistry-based routes is notoriously difficult. The present work demonstrates that Sr2FeMoO6 can be mechanosynthesized at ambient temperature in air directly from its precursors (SrO, -Fe, MoO3) in the form of nanostructured powders, without the need for solvents and/or calcination under controlled oxygen fugacity. The mechanically induced evolution of the Sr2FeMoO6 phase and the far-from-equilibrium structural state of the reaction product are systematically monitored with XRD and a variety of spectroscopic techniques including Raman spectroscopy, 57Fe Mössbauer spectroscopy, and X-ray photoelectron spectroscopy. The unique extensive oxidation of iron species (Fe0  Fe3+) with simultaneous reduction of Mo cations (Mo6+  Mo5+), occuring during the mechanosynthesis of Sr2FeMoO6, is attributed to the mechanically triggered formation of tiny metallic iron nanoparticles in superparamagnetic state with a large reaction surface and a high oxidation affinity, whose steady presence in the reaction mixture of the milled educts initiates/promotes the swift redox reaction. High-resolution transmission electron microscopy observations reveal that the mechanosynthesized Sr2FeMoO6, even after its moderate thermal treatment at 923 K for 30 min in air, exhibits the nanostructured nature with the average particle size of 21(4) nm. At the short-range scale, the nanostructure of the as-prepared Sr2FeMoO6 is characterized by both, the strongly distorted geometry of the constituent FeO6 octahedra and the extraordinarily high degree of anti-site disorder. The degree of anti-site disorder ASD = 0.5, derived independently from the present experimental XRD, Mössbauer, and SQUID magnetization data, corresponds to the completely random distribution of Fe3+ and Mo5+ cations over the sites of octahedral coordination provided by the double perovskite structure. Moreover, the fully anti-site disordered Sr2FeMoO6 nanoparticles exhibit superparamagnetism with the blocking temperature TB = 240 K and the deteriorated effective magnetic moment  = 0.055 B per formula unit.